One‐Pot Combination of eROP and ROMP for the Synthesis of Block Copolymers. Issue 21 (9th October 2015) - Jiang, Wei; An, Ni; Zhang, Qiuping; Xiang, Shidong; Bai, Zhenguo; Han, Haobo; Li, Xuesong; Li, Quanshun; Tang, Jun
Abstract : The one‐pot combination of enzymatic ring‐opening polymerization (eROP) and ring‐opening metathesis polymerization (ROMP) is successfully established to construct block copolymers. cis ‐1, 4‐Diacetoxy‐2‐butene is employed both as a precursor to initiate eROP of ε ‐caprolactone or 15‐pentadecanolide and as a chain transfer agent in ROMP. The obtained polymers are systematically characterized by NMR, GPC, DSC, and microTOF‐QII MS. An evaluation of the reaction kinetics indicates the presence of two stages during the one‐pot eROP/ROMP process. Compared with cascade methods, this one‐pot method exhibits many advantages for preparing well‐defined block copolymers, such as mild reaction conditions and the elimination of complex purification steps for intermediates. Thus, this one‐pot combination approach has the potential to be widely used in preparing biocompatible polymeric materials, especially for biological and pharmaceutical applications. Abstract : The one‐pot combination of eROP and ROMP is successfully conducted to prepare block copolymers. The strategy possesses many advantages for preparing well‐defined copolymers, such as mild reaction conditions and the elimination of purification steps for complex intermediates.